Piloting a community health and well-being worker model in Cornwall: a guide for implementation and spread - John Tredinnick-Rowe; Richard Byng; Tamsyn Brown; Donna Chapman (BMC Primary Care)
Abstract Background This paper evaluates the introduction of ten Community Health and Well-being Workers (CHWW) in four pilot sites across Cornwall. The period evaluated was from the initial start in June 2022 until June 2023, covering the project setup and implementation across a range of Primary Care Networks (PCNs) and Voluntary sector partners (VSCO). Methods All ten CHWWs and their managers at each site were interviewed (n = 16) to understand the barriers and enablers to implementation and wider learning that could be captured around the project setup. Qualitative methods were used for data collection, including semi-structured interviews and focus groups. Transcripts were thematically analysed for cross-cutting themes, as well as site-specific effects. Results In terms of learning, we cover the following key areas, which were of most importance to the successful implementation of the pilot: The CHWWs were introduced into an already established, successful social prescribing (SP) system by the time the CHWW project began. CHWWs can access some of the same training and office space as SPs, with overlapping meeting schedules allowing them joint input on some topics. It seemed that all the pre-work in terms of relationships and learning about a similar role helped a rapid implementation. Each site’s CHWW management structure uses the same line management as the SPs. Roles were clustered together to remove duplication, maximise coverage and triaging of residents. The largest barrier to overcome was integrating VSCO staff into NHS systems. Conversely, hosting CHWWs within an NHS organisation has pros and cons, namely better access to NHS data and staff, but longer lead-in time for registration on systems, and more bureaucracy for procurement/spend. Conclusions Looking to the future, the pilot’s success has spread the programme to other integrated care areas in the country, with ongoing plans for further rollout and evaluation in the coming years.